Comorbidities as predictors of incidental prostate cancer after Holmium laser enucleation of the prostate: diabetes and high-risk cancer. (2nd October 2017) - Ohwaki, Kazuhiro; Endo, Fumiyasu; Shimbo, Masaki; Fujisaki, Akiko; Hattori, Kazunori
Abstract: Prostate cancer can be diagnosed as an incidental finding during the pathological examination of benign prostatic hyperplasia (BPH) specimens by Holmium laser enucleation of the prostate (HoLEP). BPH and comorbidities such as hypertension, diabetes, and dyslipidemia often coexist in elderly people. We identified which comorbidities can be used to predict the presence of incidental prostate cancer, particularly high-risk cancer, in men who had undergone HoLEP. On the basis of pathological findings of HoLEP specimens, patients with incidental cancer were categorized as low-risk (Gleason ≤6 and T1a) or high-risk (all others). Of the 654 patients who underwent HoLEP, 41 patients (6.3%) were identified as having incidental cancer (25 low-risk and 16 high-risk). There were no significant factors for overall prostate cancers. However, a significantly higher frequency of diabetes was observed in patients with high-risk cancer compared to those with BPH (31% vs. 13%; p  = .033). Logistic regression analysis using prostate-specific antigen (PSA) and prostate volume (PV), and smoking showed that diabetes was an independent predictor of high-risk cancer (odds ratio, 3.15; 95% confidence interval, 1.06–9.43). Diabetes may be an important predictor of the presence of high-risk prostate cancer in men with BPH who have undergone HoLEP.